A Correlated Random-Field Ising Model for Pore-Scale Hysteresis in Soil-Water Characteristic Curves - Gómez Azuero, Angela Viviana; Salazar Montenegro, Juan Carlos (Civil Engineering Journal, 2026)
The soil–water characteristic curve (SWCC) plays a central role in the behavior of unsaturated soils, yet explaining its hysteresis directly from pore-scale mechanisms remains challenging. The objective of this study is to investigate how pore-size heterogeneity, spatial correlations, and cooperative dynamics contribute to hysteresis in SWCCs. In this study, a correlated Random-Field Ising Model (RFIM) combined with Monte Carlo simulations is developed to represent the pore space as a two-dimensional lattice with a bimodal distribution of pore volumes and a spatially correlated disorder field. Drainage processes are simulated without parametric curve fitting, enabling direct analysis of pore-scale switching dynamics. The results show that macropore fraction, pore-size heterogeneity, and the activation parameter β exert a strong control on drainage behavior. Low β values produce smooth and nearly reversible drainage, whereas higher β stabilizes metastable pore configurations and yields abrupt transitions accompanied by hysteresis. The divergence between number-based and volume-based saturation serves as a useful indicator of size-selective drainage and cooperative pore-scale events. The novelty of this work lies in providing a physically grounded and statistically dynamics to macroscopic hysteresis in SWCCs, offering insights beyond traditional phenomenological or uncorrelated pore-network approaches.